(untitled) (The Review of Diabetic Studies, 2024)
Background: Family presence during intensive care is increasingly recognized as a core component of patient-centered care, yet its impact on nursing practice in Saudi Arabia remains underexplored. Objective: This study examined ICU nurses’ perceptions of family presence and its influence on nursing practice, workflow, professional satisfaction, and patient outcomes in Saudi Arabian hospitals. Methods: A cross-sectional survey was conducted among 250 registered nurses working in adult ICUs across public and private hospitals. Participants reported demographic characteristics, perceptions of family involvement, and its effects on nursing practice, workflow, and patient care. Descriptive statistics were used to analyze responses. Results: The majority of nurses were female (72%), with a mean age of 31.6 ± 6.8 years and an average ICU experience of 5.4 ± 3.2 years. Between 89% and 94% strongly agreed that family presence positively influences patient outcomes, enhances communication, supports patient-centered care, and improves professional satisfaction. While 89% acknowledged increased emotional and cognitive workload, most nurses emphasized that the benefits of family involvement outweigh the challenges. Institutional support, clear policies, adequate staffing, training, and cultural sensitivity were identified as key enablers for successful family-centered care. Conclusion: ICU nurses in Saudi Arabia perceive family presence as highly beneficial for both patient care and professional practice. Implementation of family-centered care is recommended, supported by structured policies, education, sufficient resources, and culturally sensitive practices. These findings highlight the potential for family involvement to enhance ICU care quality and nursing satisfaction.